“Enhancing Children’s Creative and Cultural Competencies through Folk Applied Arts” - Raxmonova Rayxon Zoir qizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article examines the use of folk applied arts to enhance creative and cultural competencies in school-age children. The study highlights practical activities such as creating traditional patterns, combining colors, and presenting work, which promote children’s visual thinking, aesthetic taste, and appreciation of cultural heritage. The findings suggest that integrating folk arts into the curriculum fosters children’s creativity, social skills, and respect for national traditions, providing an effective pedagogical approach for holistic development.